Elections Matter: the Politics of Prosecuting Deceptive Advertising in Wisconsin - (:unkn) unknown (My University, 2016)
This study examines the causal relationship between ideology and regulation. Specifically, this study looks at the relationship between Wisconsin elected officials and their political party in relation to the level of enforcement of the Wisconsin deceptive advertising statute. The study analyzed 79 Wisconsin cases prosecuted for deceptive advertising from 2003 through 2014. The 79 cases occurred over the span of three different governor and attorney general four-year periods.These cases were analyzed for outcomes and the number of cases prosecuted during each of the three four-year periods present in Wisconsin. Fifty-six of the 79 cases were analyzed further for the number of defendants, type of defendants, amount of forfeitures ordered by the court during each four-year period. The study found that the part of the governor and attorney general correlated with the number of deceptive advertising cases prosecuted and the amount of forfeiture ordered in a four-year period.
Keywords: Deceptive Advertising; Regulation